Pesan Dakwah dalam Kegiatan Mangupa-Upa Adat Batak Angkola Di Dusun Payagoti - Ani Siregar; Asrul Harahap (CV. ALIM'SPUBLISHING, 2026)
This study is motivated by the existence of the mangupa-upa tradition among the Batak Angkola people, which serves not only as a traditional ritual but also as a medium for conveying Islamic missionary values rich in spiritual and moral significance. Amidst the tide of modernization, there is a tendency for a shift in the meaning and practice of this tradition, thus requiring an in-depth study to understand the da’wah values contained within it. The objective of this study is to analyze the messages of Islamic da’wah found in the mangupa-upa tradition as well as the symbolic meanings that accompany them in community life. The method used is field research with an anthropological approach and a descriptive qualitative research design. Data were collected through observation and in-depth interviews with informants selected through purposive sampling, then analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. Research findings indicate that the Mangupa-upa tradition contains religious messages encompassing aspects of worship and moral conduct. In the context of worship, this tradition emphasizes the importance of sincere devotion to God, prayer, maintaining regular prayer, and cultivating a sense of gratitude in daily life. Meanwhile, from the perspective of moral values, Mangupa-upa teaches the importance of politeness, respect for elders, loyalty within the family, social responsibility, and the encouragement to always be humble and help one another. Furthermore, the Mangupa-upa tradition within the Batak Angkola customs, particularly in the village of Payagoti, is rich with symbols that carry profound philosophical meanings and align with Islamic values. These symbols include the buffalo head, symbolizing strength and sacrifice; the chicken, representing vigilance and courage; salt, as the bond of life; the egg, a symbol of fertility; the fish, representing sustenance and harmony; and the shrimp, a symbol of humility. Additionally, there is colored rice as a symbol of diversity, the banana tree as resilience, the siri leaf as honor, the ulos as compassion, the banana leaf as protection, water as purity, and the gambir leaf as steadfastness in life.